Emotional State Recognition Using Facial Expression, Voice, and Physiological Signal - DJARA, Tahirou; Ousmane, Abdoul Matine; VIANOU, COKOU ANTOINE (My University, 2018)
Emotion recognition is an important aspect of affective computing, one of whose aims is the study and development of behavioral and emotional interaction between human and machine. In this context, another important point concerns acquisition devices and signal processing tools which lead to an estimation of the emotional state of the user. This article presents a survey about concepts around emotion, multimodality in recognition, physiological activities and emotional induction, methods and tools for acquisition and signal processing with a focus on processing algorithm and their degree of reliability.
Keywords: Affective computing; emotion recognition; Multimodal interaction; ...